ACM and IEEE contribution to curriculum change in computer science - Sobral, Sónia Rolland (2020)
The first curriculum studies for undergraduate studies in Computer Science appeared in March 1968, when the Association for Computing Machinery (ACM) published an innovative and necessary document, Curriculum 68: Recommendations for academic programs in computer science. Since then, efforts have been made to make curriculum recommendations for universities around the world. In 1991, IEEE (Institute of Electrical and Electronics Engineers) and ACM joined to publish a new document, computing curricula 1991: report of the ACM/IEEE-CS Joint Curriculum Task Force. In 2005, with the Computing Curriculum 2005: The Overview Report, there was made a distinction between Computer Engineering (CE), Computer Science (CS), Information Systems (IS), Information Technology (IT), and Software Engineering (SE). In this way, the new curriculum reports have come to focus on a specific area, and there is a departure from the core and elective areas by each of the specific cases. (...)